Temporal Variations in Cigarette Tobacco Bacterial Community Composition and Tobacco-Specific Nitrosamine Content Are Influenced by Brand and Storage Conditions - Chopyk, Jessica; Chattopadhyay, Suhana; Kulkarni, Prachi; Smyth, Eoghan M.; Hittle, Lauren E.; Paulson, Joseph N.; Pop, Mihai; Buehler, Stephanie S.; Clark, Pamela I.; Mongodin, Emmanuel F.; Sapkota, Amy R. (Frontiers in Microbiology, 2017)
Tobacco products, specifically cigarettes, are home to microbial ecosystems that may play an important role in the generation of carcinogenic tobacco-specific nitrosamines (TSNAs), as well as the onset of multiple adverse human health effects associated with the use of these products. Therefore, we conducted time-series experiments with five commercially-available brands of cigarettes that were either commercially-mentholated, custom-mentholated, user-mentholated or non-mentholated. To mimic user storage conditions, the cigarettes were incubated for 14 days under three different temperatures and relative humidities (i.e., pocket, refrigerator and room). Overall, 360 samples were collected over the course of two weeks and total DNA was extracted, PCR amplified for the V3V4 hypervariable region of the 16S rRNA gene and sequenced using Illumina MiSeq. A subset of samples (n=32) was also analyzed via liquid chromatography with tandem mass spectrometry for two TSNAs: N'- nitrosonornicotine (NNN) and 4-(methylnitrosamino)-1-(3-pyridyl)-1-butanone (NNK). Comparative analyses of the five tobacco brands revealed bacterial communities dominated by Pseudomonas, Pantoea, and Bacillus, with Pseudomonas relatively stable in abundance regardless of storage condition. In addition, core bacterial operational taxonomic units (OTUs) were identified in all samples and included Bacillus pumilus, Rhizobium sp., Sphingomonas sp., unknown Enterobacteriaceae, Pantoea sp., Pseudomonas sp., Pseudomonas oryzihabitans, and Pseudomonas putida. Additional OTUs were identified that significantly changed in relative abundance between day 0 and day 14, influenced by brand and storage condition. In addition, small but statistically significant increases in NNN levels were observed in user- and commercially-mentholated brands between day 0 and day 14 at pocket conditions.. These data suggest that manufacturing and user manipulations, such as mentholation, and storage conditions, may directly impact the microbiome of cigarette tobacco as well as the levels of carcinogens.